2014
DOI: 10.5137/1019-5149.jtn.10884-14.2
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral thalamic glioma - case report and review

Abstract: diagnosis reported as 3 years in patients with grade II BLTG (2,10).We present the case of a BLTG manifesting with fast progressive cognitive dysfunction leading to dementia in an elderly patient. █ CASE REpORTA 72-year-old right handed male, treated only for essential arterial hypertension stage I, presented 3 months prior to admittance, with gradual deterioration of the cognitive functions and intermittently aggressive behavior towards close relatives. The symptoms progressed gradually, with the patient not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The prevalence of neurodegenerative disorders is continuously increasing as a consequence of the dramatic rise in life expectancy due to scientific achievements and progress, thus posing a significant threat to human health [ 5 , 7 , 9 , 10 ]. Moreover, neurodegeneration is associated with various neurodegenerative, neurotraumatic, and neuropsychiatric disorders, with considerably diverse pathophysiology, including memory and cognitive impairments, muscle weakness and/or paralysis, abnormal control of the voluntary movement, seizures, confusion, and pain [ 2 , 4 , 7 , 11 , 12 , 13 ]. Specifically, such diseases vary from progressive degenerative disorders, including Alzheimer’s disease (AD), Parkinson’s disease, Huntington’s disease, amyotrophic lateral sclerosis and multiple sclerosis [ 4 , 5 , 10 , 14 , 15 ], to acute traumatic injuries, such as traumatic brain injury, stroke or spinal cord injury [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of neurodegenerative disorders is continuously increasing as a consequence of the dramatic rise in life expectancy due to scientific achievements and progress, thus posing a significant threat to human health [ 5 , 7 , 9 , 10 ]. Moreover, neurodegeneration is associated with various neurodegenerative, neurotraumatic, and neuropsychiatric disorders, with considerably diverse pathophysiology, including memory and cognitive impairments, muscle weakness and/or paralysis, abnormal control of the voluntary movement, seizures, confusion, and pain [ 2 , 4 , 7 , 11 , 12 , 13 ]. Specifically, such diseases vary from progressive degenerative disorders, including Alzheimer’s disease (AD), Parkinson’s disease, Huntington’s disease, amyotrophic lateral sclerosis and multiple sclerosis [ 4 , 5 , 10 , 14 , 15 ], to acute traumatic injuries, such as traumatic brain injury, stroke or spinal cord injury [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to Ravindren, patients who experienced recanalization within the first six hours have a better outcome [40]. Separately, a large multicentre study including 592 patients presenting with ABAO demonstrated that a worse outcome would likely be achieved if recanalization were to take more than nine hours [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…10 plots fluence dependent absorption of CaF2 optics without SSD (left plot, FemtoFinish) and with SSD (right plot, conventional polish) at 193 nm [5]. The fluence dependent absorption was determined by using a laser calorimetric measurement, based on the absorption-induced heating of a tested sample under laser irradiation [6,7]. The fluence dependent absorptance measurements were conducted by first increasing the laser fluence to 50 mJ/cm 2 with a step increment of 5 mJ/cm 2 .…”
Section: Subsurface Damage and Two-photon Absorptionmentioning
confidence: 99%